Kritik Matan Hadis dengan Pendekatan Al-Qur’an: Studi Pemahaman Muḥammad Al-Ghazālī dan Jamāl Al-Bannā - Agung Abdillah; Rizal Alwi Mampa (Refleksi, 2019)
Matan ḥadīth criticism is not new in the scientific world of ḥadīth, criticism of matan ḥadīth has been done since the time of the Prophet and the companions and then continued until the present. The existence of criticism of traditions in the history of traditions must have been born along with the number of persons who misuse the function of ḥadīth to the rise of counterfeiting of traditions to achieve irresponsible interests. The figures to be discussed are figures that are considered controversial for some people, because these two figures reject the authentic hadith that contradicts its meaning with the Qur’an. Therefore the author here feels the need for a review of the understanding of these two figures related to their understanding of the traditions, hadith aḥad, and the methodology of understanding the traditions with the Qur’anic approach.